2014
DOI: 10.7448/ias.17.1.18994
|View full text |Cite
|
Sign up to set email alerts
|

Towards elimination of mother‐to‐child transmission of HIV: performance of different models of care for initiating lifelong antiretroviral therapy for pregnant women in Malawi (Option B+)

Abstract: IntroductionMalawi introduced a new strategy to improve the effectiveness of prevention of mother-to-child HIV transmission (PMTCT), the Option B+ strategy. We aimed to (i) describe how Option B+ is provided in health facilities in the South East Zone in Malawi, identifying the diverse approaches to service organization (the “model of care”) and (ii) explore associations between the “model of care” and health facility–level uptake and retention rates for pregnant women identified as HIV-positive at antenatal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 6 publications
3
72
1
Order By: Relevance
“…However, the model of integration in high prevalence, low resource contexts may also have an impact on downstream retention. Our current analysis confirms the finding from an earlier health facility-level analysis in an operational setting, where we observed that model of care had impact on retention in care [6], with worse program indicators in facilities in which women receive the first dose of ART at the ANC clinic and are then transferred to the ART clinic for ART follow-up.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the model of integration in high prevalence, low resource contexts may also have an impact on downstream retention. Our current analysis confirms the finding from an earlier health facility-level analysis in an operational setting, where we observed that model of care had impact on retention in care [6], with worse program indicators in facilities in which women receive the first dose of ART at the ANC clinic and are then transferred to the ART clinic for ART follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…Health facilities therefore made decisions about the organization of PMTCT care on the basis of factors related to their specific circumstances. A previous study describing and comparing Option B+ service delivery models in six of Malawi's twenty-eight districts using facility-level MOH cohort reports demonstrated large variability in how services had been integrated and observed associations between the organization of service delivery and both uptake of HIV testing and retention in care on ART [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Regarding integration of ANC and ART care, van Lettow et al . found that facilities, which require a referral between ANC and ART for all doses of ART had a higher rate of retention of women at 12 months after ART initiation than facilities where either the first or all doses of ART were provided in the ANC facility [23] (Table 8). Similarly, Weigel et al .…”
Section: Resultsmentioning
confidence: 99%
“…In sub-Saharan Africa, despite high antenatal care (ANC) utilization, 1 bottlenecks occur at each step of the PMTCT cascade, from HIV testing of pregnant women, to uptake of antiretrovirals (ARVs) or combination antiretroviral therapy (cART), to screening HIV-exposed infants (HEI) with HIV polymerase chain reaction (PCR) testing, to adoption and maintenance of appropriate infant feeding. 24 Facility-level barriers include human resources shortages, 5 lack of service integration, 3,5,6 lack of ongoing mentoring, 7 and poor patient-provider interactions. 5 Though vertical transmission rates of <1% have been achieved in high-income countries, 8 actual rates in sub-Saharan Africa are estimated to be several times higher.…”
Section: Introductionmentioning
confidence: 99%